SOSIOLOGI SASTRA DAN NILAI PENDIDIKAN KARAKTER NOVEL THE KING ETERNAL MONARCH 1 - Pradika Kuthut Dwi Mahendra; Cahyo Hasanudin; Ali Mujahidin (Universitas Terbuka, 2022)
Novel is a literary work that describes the socio-cultural life and values ​​of life in society. The aims of this study are: 1.) To describe the socio-historical of the author, 2.) To describe the influence of events in the novel on society based on social aspects, 3.) To describe the reader's response to the contents of the novel, 4. ) To describe the value of character education in the novel, 5.) Describing the relevance of novels in learning literature in high school. The research method used is descriptive-qualitative with a sociology of literature approach. The results obtained in this study are: 1.) The King Eternal Monarch 1 novel was born from a writer who tends to always choose the romance genre that is packaged with fantasy, social and cultural fiction. 2.) Readers of The King Eternal Monarch 1 novel tend to like this novel because of its strong character packaging and unpredictable plot. 3.) The King Eternal Monarch 1 novel can have a good influence on society through emerging social aspects including, Religious Aspects, Political Aspects, Leadership Aspects and Economic Aspects. 4.) The King Eternal Monarch 1 novel contains character education values ​​according to the statement of the Ministry of National Education (2010) including honesty, religious, discipline, hard work and independence. 5.) The implementation of social values ​​and character education is appropriate and relevant to be used as literature teaching materials in high school.